THU0406 Iv cyclophosphamide vs. rituximab for the treatment of early diffuse scleroderma lung disease: open label, randomised, controlled trial. (12th June 2018) - Sircar, G.; Goswami, R.P.; Sircar, D.; Rath, D.; Mondal, S.; Mahapatra, P.S.; Ghosh, A.; Ghosh, P.
Abstract : Background: Systemic sclerosis is characterised by fibrotic changes in the skin and lung, and the mainstay of treatment has been cyclophosphamide. B cell involvement suggests that rituximab may also be of therapeutic benefit. In this study, we compared the safety and efficacy of rituximab compared to cyclophosphamide in the treatment of skin and lung manifestations of systemic sclerosis. Objectives: The aims of the study were to assess the efficacy and safety of IV Rituximab compared to IV cyclophopsphamide in the primary therapy of systemic sclerosis, with particular emphasis on pulmonary and dermatological manifestations. Methods: We randomly assigned 60 patients of systemic sclerosis, age 18–70 years with skin and lung involvement, to monthly pulses of cyclophosphamide 500 mg/sq. m or rituximab 1000 mg x 2 doses at 0, 15 days. Primary outcomes were forced vital capacity (FVC) percent predicted at six months. Secondary outcomes were: absolute change in litres (FVC-L) at six months; modified Rodnan Skin Scores at 6 months, six-minute walk test (6MWT), and Medsgers score Results: The FVC (%mean ±SD) in Rituximab group improved from 61.30 (±11.28) to 67.52 (±13.59) while in Cyclophosphamide group, it declined from 59.25 (±12.96) to 58.06 (±11.23) at 6 months (p 0.003). The change of FVC was 1.51 (±0.45) L to 1.65 (±0.47) L in Rituximab group compared to 1.42 (±0.49) to 1.42 (±0.46) L in Cyclophosphamide group. The mRSS changed from 21.77 (±9.86) to 12.10 (±10.14) in RTX group and 23.83 (±9.28) to 18.33 (±7.69) in Cyclophosphamide group after 6 months. Serious adverse events were more common in the cyclophosphamide group. Conclusions: Rituximab is a safe and effective alternative to cyclophosphamide in the primary therapy of skin and lung manifestations of scleroderma. Disclosure of Interest: None declared